Artemisia jacutica Drob. essential oil as a source of chamazulene: primary introduction and component analysis - Elena P. Dylenova; Svetlana V. Zhigzhitzhapova; Danaya B. Goncharova; Zhargal A. Tykheev; Daba G. Chimitov; Larisa D. Radnaeva (Foods and Raw Materials, 2023)
Artemisia jacutica Drob. is a valuable source of chamazulene, which has anti-inflammatory and antioxidant properties. We experimentally introduced this plant in the climatic conditions of Buryatia and compared the compositions of the essential oils produced from both cultivated and wild plants. The reserves of A. jacutica and the laboratory/field germination of seeds were assessed by standard methods. Macro- and microscopic features were determined in line with general pharmacopoeia monographs. The composition of the essential oil obtained by hydrodistillation was analyzed by gas chromatography–mass spectrometry. The resulting data were processed by the principal component method. The antiradical activity was measured by the DPPH test. The reserves of A. jacutica were determined in the Yeravninsky district of Buryatia. The laboratory germination of A. jacutica seeds was 75.00 ± 5.35%, while the field germination was only 11–23%. Planting with seedlings showed a good survival rate of 67–80%. In the first year of cultivation, A. jacutica plants had similar macro- and microscopic features to those of wild plants. The soils from the experimental plots were superior to the soils of A. jacutica’s natural habitat in terms of fertility. The essential oils from cultivated and wild plants contained 51 components. The content of chamazulene, the dominant component, was 59.22–66.60% in the cultivated plants and only 15.98–47.77% in the wild plants. The essential oil of A. jacutica exhibited high antiradical activity (IC50 = 49.47 μL/mL). The primary introduction of A. jacutica showed good prospects for its cultivation in Buryatia. The macro- and microscopic features and dominant components found in the essential oil of A. jacutica grown on the experimental plots were similar to those found in the wild plants. Two chemotypes of A. jacutica, Yakutian and Buryatian, were identified according to the oil composition, with the chemotypes preserved in the cultivated plants. The oil’s high antiradical activity and a high content of chamazulene make A. jacutica a valuable material for the cosmetic, pharmaceutical, and agricultural industries.